An age-dependent selective maintenance policy for a gas processing plant in Vietnam - Nguyen Kim Ngoc; Huynh, Trung Luong; Voratas Kachitvichyanukul; PetroVietnam (Pathum Thani : Asian Institute of Technology, 2010)
This project researched a selective maintenance policy founded on the components age of the system. In this maintenance policy, we will fix the operation period and carry out the system maintenance in a short period before the next operation cycle. During this defined time, some maintenance actions, for example: the replacement of an identical item, the rehabilitation or doing nothing actions will be considered and realized for each component. Due to the fixed maintenance period is usually not enough for maintenance of all components in the system, only some components are selected for maintenance during that period in order to maximize availability. A mathematical model is proposed to help maximize system the availability according to the time and budget constraints of preventive maintenance. This model is executed for a serial-parallel system and then applied for the maintenance problem at a gas processing plant in Vietnam. @Risk Optimizer program is used for solution purpose. From numerical and sensitivity analysis results, some recommendations are also derived.
Submitted in partial fulfillment of the requirements for the Degree of Professional Master of Engineering in Industrial Engineering and Management, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2010
Keywords: Plant maintenance -- Vietnam; Maintenance -- Vietnam